Adaptive sliding-mode controller of a lower limb mobile exoskeleton for active rehabilitation. (March 2021) - Pérez-San Lázaro, Rafael; Salgado, Ivan; Chairez, Isaac
Abstract: This study describes the design, instrumentation and control of an exoskeleton for lower limb children rehabilitation with nine degrees of freedom. Three degrees of freedom in each leg exert the movements of hip, knee and ankle in the sagittal plane, and three control the drive track system composed by a caterpillar-like robot. The control scheme presents a model free decentralized output feedback adaptive high-order sliding mode control to solve the trajectory tracking problem in each degree of freedom of the exoskeleton. A high order sliding mode differentiator estimates the unmeasured states and, by means of a dynamical state extension, it approximates the unknown dynamical model of the exoskeleton. A second-order adaptive sliding mode controller based on the super-twisting algorithm drives the exoskeleton articulations to track the proposed reference trajectories, inducing an ultimate boundedness for the tracking error. Numerical and experimental simulation results demonstrate the effect of the adaptive gain on the super-twisting control design. Such evaluations confirmed the superior tracking performance forced by the adaptive law for the controller with a smaller chattering amplitude and smaller mean tracking error. Highlights: The exoskeleton includes 9 DoF, 3 in each leg and 3 in the displacement system. The device can displace on flat terrains, while exerting lower-limbs movement. A decentralized output feedback adaptive high-order sliding mode control is applied. Numerical simulation results demonstrate the effect of the adaptive gain. Experimental results show the implementation on a self-constructed exoskeleton